Plan de negocio para el lanzamiento de un producto farmacéutico en la categoría microorganismos antidiarreicos - Salazar Miranda, Adrián Javier (2016)
The following business plan is based on the launch of a pharmaceutical antidiarrheal product, Saccharomyces boulardii, molecule that neutralizes diarrhea without adverse effects and with proven therapeutic benefits. To analyze and assess the feasibility of creating a company which is responsible for creating a specific formula for an outsourced company to perform the production. Subsequently, the distribution of the finished product will be delivering to another company to be responsible for product placement in the points of purchase. The company, which owns the medication formula, will be responsible of the commercialization of the product in the pharmaceutical market in the province of Pichincha. For the development of the following business plan it was consider the guiding principles of the Universidad de las Americas; the regulations of the degree dissertation, rubric, APA rules, index and tame frame of the degree dissertation. The guidance of tutor was key to the development and implementation of this business plan. The results of this business plan are crucial to the viability of the project regarding the different aspects of analysis in the course of this document such as; introduction, analysis, customer analysis, business opportunity, marketing plan, organizational structure, financial evaluation and conclusions. The financial indicators determine the final decision whether to implement the project or not. After the project study has been completed, it concludes the implementation of this business plan.